CAUSE AND EFFECT OF SUFFERING IN SYDNEY SHELDON’S NOVEL IF TOMORROW COMES - Muarif Setiawan; Efendi Barus; M. Ali Pawiro (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2017)
Abstract  If Tomorrow Comes, a novel written by Sydney Sheldon, is a story of intrigue and revenge. Tracy Whitney is a young, beautiful and intelligent woman and about to marry a wealth man until, suddenly, she is betrayed, framed by a ruthless Mafia gang, and then abandoned by the man she loves. Only her ingenuity saves her and helps her fight back. The significant theme of the novel is suffering, which is the focus of the study with two major points of discussion: the causes and the effects of suffering, subdivided into avarice and loss of trust as a part of the first major point and courage, revenge and hypocrisy as the second major one. The study is conducted with descriptive qualitative method proposed by Dawson (2004) pointing out that qualitative descriptive research is appropriately used to analyze social phenomena. The result shows that the protagonist, Tracy Whitney, faces a lot of suffering from the beginning of the story; that is from the tragic of her mother’s death till she is out of jail. All the sufferings are triggered by avarice of a small group of bandits of white collars having a great personal interest who stand against Tracy and loss of trust from her fiancé, the one whom she expects to be with her in time of difficulty. Owing to her sufferings, Tracy becomes strong mentally but she also turns to be revengeful woman of significant hypocrisy. Keywords: suffering, avarice, trust, courage, revenge and hypocrisy.